Diagnosa penyakit dan analisis kualitas air untuk kesehatan ikan Nila (Oreochromis niloticus) yang dipelihara pada keramba jaring apung - Handayani, Leni; ., Siswanto (Universitas Sam Ratulangi, 2022)
The purpose of this study was to diagnose diseases that attack tilapia and analyze the quality of the waters around the floating net cages. The research was conducted using in situ and ex situ methods. Sampling was carried out in Pematang Limau Village, while for disease diagnosis at the PUSKESWAN Laboratory and water chemistry analysis at the Health and Calibration Laboratory of Palangka Raya. Diagnosis is made by taking fish samples and observing the clinical symptoms of fish. Disease diagnosis included parasitic and bacterial diseases. For water quality parameters, physical and chemical parameters of the waters were observed. Based on the diagnostic results of observations in the field and in the laboratory, a conclusion was obtained that the tilapia (Oreochromis niloticus) reared in floating net cages in Pematang Limau Village did not experience specific diseases because the symptoms showed only bleeding and lumps on the skin, side of the mouth of some fish only. Laboratory results from the identification of the disease for bacterial diseases were not found, only parasitic diseases with a mild attack level with 4 types of ectoparasites that often attack tilapia. The results of the analysis of water quality in the waters also showed relatively good, but when viewed from the BOD and COD values, it shows that there was light water pollution.